2010
DOI: 10.4269/ajtmh.2010.09-0327
|View full text |Cite
|
Sign up to set email alerts
|

Association of Microsatellite Variations of Plasmodium falciparum Na+/H+ Exchanger (Pfnhe-1) Gene with Reduced In Vitro Susceptibility to Quinine: Lack of Confirmation in Clinical Isolates from Africa

Abstract: Abstract. We sought to test the association of polymorphisms in Plasmodium falciparum nhe-1 ( Pfnhe-1 , gene PF13_0019) with in vitro susceptibility to quinine, which was previously reported in a limited number of reference strains or culture-adapted isolates. Determination of in vitro susceptibility to quinine, genotyping of Pfnhe-1 ms4760 microsatellite and polymorphism in codon 76 of Pfcrt were performed for 83 isolates obtained from symptomatic malaria-infected travelers returning from various African coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
36
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 17 publications
6
36
1
Order By: Relevance
“…As expected and found in previous studies, four alleles (ms4760-1, ms4760-3, ms4760-6, and ms4760-7) were predominant in both countries. 14,15,[17][18][19][20][21][22] However, significant differences in the distribution and prevalence of allele were observed both between countries and within sites in the Comoros ( Table 1). The genetic diversity of the ms4760 allele observed in our study was similar between both countries (0.84 and 0.85), and it was comparable with the genetic diversity previously described in African (Congo = 0.76, Uganda = 0.79, and Kenya = 0.66) 15,17,20 and Indian isolates (0.68) 23 and significantly higher than the diversity found in Asian isolates (China/Myanmar = 0.68, P = 0.04; Vietnam = 0.49, P 0.0001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As expected and found in previous studies, four alleles (ms4760-1, ms4760-3, ms4760-6, and ms4760-7) were predominant in both countries. 14,15,[17][18][19][20][21][22] However, significant differences in the distribution and prevalence of allele were observed both between countries and within sites in the Comoros ( Table 1). The genetic diversity of the ms4760 allele observed in our study was similar between both countries (0.84 and 0.85), and it was comparable with the genetic diversity previously described in African (Congo = 0.76, Uganda = 0.79, and Kenya = 0.66) 15,17,20 and Indian isolates (0.68) 23 and significantly higher than the diversity found in Asian isolates (China/Myanmar = 0.68, P = 0.04; Vietnam = 0.49, P 0.0001).…”
mentioning
confidence: 99%
“…The mechanism underlying QN resistance is not well-understood, and it is probably complex and multigenic. Since the seminal work by Ferdig and others 13 in 2004, 11 studies have been conducted in different countries to evaluate implication of ms4760 polymorphisms in QN resistance, [14][15][16][17][18][19][20][21][22][23][24] and conflicting data have been reported, likely because of the different geographical origin of parasites (implying different genetic backgrounds), the type of parasites used (fresh isolates, culture-adapted strains, and reference lines), and the method used to assess in vitro QN susceptibility. 21,25 In this context and to extend our previous work regarding ms4760 polymorphisms in Plasmodium falciparum parasites circulating in malaria-endemic areas in the Indian Ocean, 14 we have analyzed ms4760 sequences from 595 isolates (Madagascar, N = 345; Comoros, N = 250).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence polymorphisms in the Pfnhe1 gene have been analyzed in laboratory strains and field isolates with varied susceptibilities to QN (16,(24)(25)(26)(27). Several variants of ms4760 have been described in which ms4760 -1, with 2 copies of the DNNND repeat unit, was significantly associated with reduced in vitro QN sensitivity in laboratory clones (16) and in field isolates (24).…”
mentioning
confidence: 99%
“…Yet a study of 108 field isolates showed a lack of evidence for a selective sweep in flanking microsatellites of the gene, suggesting a lack of intensive selection pressure typical of a major dominant resistance gene (7). Conversely, an association between the DNNND repeat polymorphism within the Pfnhe-1 microsatellite and quinine susceptibility has been repeatedly confirmed with culture-adapted isolates (15,18,22), while investigations based on fresh isolates either failed to confirm (2,6) or substantiated (28) this association.…”
mentioning
confidence: 99%